POLA PELIBATAN WANITA DALAM KELOMPOK MASYARAKAT PROGRAM INPRES DESA TERTINGGAL (POKMAS IDT) DI KABUPATEN LOMBOK TIMUR - Nahdi, Khirjan (Universitas Hamzanwadi, 2009)
Domination of gender has occurred in jobs and the ather things in society, in wich these is because of cultural and religion effect (Islam). The same phenomena appear is East Lombok Society, that is patriarchy and religius. Some last decades domination circumstances (problems) want to be decreased by feminisms through structural approaches. However, those approaches are not so successful, in consequentit is offered the other approaches, that is functional approaches. In East Lombok it is developed IDT Program through group approaches. It will be approved through this program wether the functional approach in more effect in reducing men domination beyond woman, wich it can be observed participating womwn in IDT Program.